Large-scale evaluation of soybean germplasm reveals geographic patterns in shade tolerance and identifies elite genotypes for intercropping systems - Fengyi Zhang; Huilong Hong; Xiulin Liu; Xueyang Wang; Chunlei Zhang; Kezhen Zhao; Rongqiang Yuan; Ahmed M. Abdelghany; Bixian Zhang; Sobhi F. Lamlom; Honglei Ren (BMC Plant Biology)
Abstract Shade tolerance is crucial for developing soybean varieties that are well-suited for intercropping systems. This study evaluated 460 soybean accessions from a global germplasm collection at two contrasting locations in China: Heilongjiang (HLJ) and Inner Mongolia (NM). The experiment used a split-plot design within a randomized complete block setup, with three replications at each site. The main plots consisted of two treatments (control and shade), and the 460 soybean accessions were randomly assigned as subplots within each treatment. Soybean genotypes were evaluated under shaded conditions (maize-soybean intercropping) and unshaded conditions (soybean monoculture) across multiple locations to assess shade tolerance and agronomic performance. Six agronomic traits were measured: plant height (PH), basal pod height (BPH), number of nodes per plant (NNP), branch number (BN), pod number per plant (PNP), and seed yield per plant (SYP). Results showed highly significant effects of location and treatment (p < 0.001) on all traits, with complex interactions between location and treatment for reproductive traits. Shade treatment triggered typical avoidance responses, increasing PH by 7.5–11.7% and BPH by 11.5–37.5%, while significantly reducing reproductive output, with PNP decreasing by 8.2–28.9% and SYP dropping by 23.9% at HLJ. Path analysis revealed a fundamental reorganization of trait contributions under shade, with NNP becoming the most critical factor for yield. Geographic differences were notable, with NM accessions showing higher shade tolerance indices compared to HLJ populations. The study identified 120 elite, stable cultivars (13.7%) that maintained consistent high performance and 100 shade-adaptive cultivars (11.4%) demonstrating enhanced plasticity. These findings provide insights into the genetic architecture of soybean shade tolerance and offer a framework for evaluating germplasm. The identified genotypes are valuable resources for developing intercropping-compatible varieties and promoting sustainable agriculture.